Pre- and Postsurgical Orthodontics in Patients with Moebius Syndrome - Marisabel Magnifico; Diana Cassi; Ilda Kasa; Marco Di Blasio; Alberto Di Blasio; Mauro Gandolfini (Hindawi Limited, 2017)
The authors report a combined orthodontic-surgical correction of an adult patient's malocclusion affected by Moebius Syndrome (MS). The treatment was conducted at the Dentistry Unit and the Maxillofacial Surgery Unit of the University Hospital of Parma. Treatment of malocclusion was performed after the correction of facial mimic mobility with smile surgery. The postoperative stability and orthodontic results were good and the correction of the morphological problems related to the syndrome was very satisfactory.